Search for independent (β/α)(4) subdomains in a (β/α)(8) barrel β-glucosidase - Almeida, Vitor M. (PLoS One, 2018)
Proteins that fold as (β/α)(8) barrels are thought to have evolved from half-barrels that underwent duplication and fusion events. The evidence is particularly clear for small barrels, which have almost identical halves. Additionally, computational calculations of the thermodynamic stability of these structures in the presence of denaturants have revealed that (β/α)(8) barrels contain two subunits or domains corresponding to half-barrels. Hence, within (β/α)(8) barrels, half-barrels are self-contained units. Here, we tested this hypothesis using β-glucosidase from the bacterium Thermotoga maritima (bglTm), which has a (β/α)(8) barrel structure. Mutations were introduced to disrupt the noncovalent contacts between its halves and reveal the presence of two domains within bglTm, thus resulting in the creation of mutants T1 (containing W12A and I217A mutations) and T2 (containing W12A, H195A, I217A and F404A mutations). Mutants T1 and T2 were properly folded, as indicated by their fluorescence spectra and enzyme kinetic parameters. T1 and wild-type bglTm were equally stable, as shown by the results of thermal inactivation, differential scanning fluorimetry and guanidine hydrochloride denaturation experiments. However, T2 showed a first-order inactivation at 80°C, a single melting temperature of 82°C and only one transition concentration (c(50)) in 2.4 M guanidine hydrochloride. Additionally, T1 and T2 exhibited a cooperative denaturation process that followed a two-state model (m-values equal to 1.4 and 1.6 kcal/mol/M, respectively), similar to that of wild-type bglTm (1.2 kcal/mol/M). Hence, T1 and T2 each denatured as a single unit, although they contained different degrees of disruption between their halves. In conclusion, bglTm halves are equivalent in terms of their thermal and chemical stability; thus, their separate contributions to (β/α)(8) barrel unfolding cannot be disentangled.